The relationship between father's involvement in breastfeeding (father's involvement) and success - Nur Azizah; Kamelia Sinaga; Rosmani Sinaga; Ribur Sinaga; Aufa Risna; Ayumahara Ayumahara; Fatiyah Fatiyah; Furie Estie Honez (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Failure to provide exclusive breastfeeding significantly increases the risk of infectious diseases in infants, particularly diarrhea, which can increase up to 30-fold. Globally, exclusive breastfeeding rates remain below established targets, including in Indonesia. In Aceh Province, exclusive breastfeeding coverage has not yet reached the national target of 80%. Various factors influence breastfeeding success, one of which is father involvement, which is currently considered the strongest external variable. Emotional and instrumental support from fathers has been shown to help regulate oxytocin levels and increase mothers' confidence in breastfeeding. Purpose: To analyze the relationship between father involvement and the success of exclusive breastfeeding. Method: This study used a quantitative method with a correlational design through a cross-sectional approach. The study was conducted from February to June 2025 in Pante Raya Village, Wih Pesam District. The study population was mothers with infants aged 7–12 months, with a purposive sampling technique of 30 respondents. The research instrument was a Likert-scale questionnaire to measure paternal involvement and an interview with infant feeding history to assess the success of exclusive breastfeeding. Data analysis was performed using the chi-square test with a 95% confidence level (p value = 0.05). Results: Univariate analysis results showed that the majority of fathers had good levels of involvement (73.3%) and most mothers were successful in providing exclusive breastfeeding (80.0%). Bivariate analysis showed that good paternal involvement was followed by a high level of exclusive breastfeeding success (95%). Chi-square test results showed a p value of 0.002 (p < 0.05). Conclusion: There is a significant relationship between father involvement and the success of exclusive breastfeeding in Pante Raya Village. Fathers' support is a crucial factor in increasing the success of exclusive breastfeeding.